IMPROVING THE ACCURACY OF BALLISTIC GRAVIMETER CHARACTERISTICS - BEZVESILNA, OLENA; NECHAI, SERGEY; HRYNEVYCH, MARIIA; TOLOCHKO, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article provides information on the conducted experimental studies of a new ballistic laser gravimeter (BLG). A detailed description of the created laboratory setup for studying the laser unit is provided, as well as a description of the procedure for adjusting and checking the laser for the size of the resonator scan. The experiments utilize measuring equipment which allowed controlling the vibration parameters of the vibration stand with an accuracy 3 times higher than the accuracy of the BLG. For a modern BLG, this amounted to an error of no more than 5% of the measured gravitational acceleration (GGA). A GGA study was conducted on the created laboratory setup. Due to the introduction of new elements into the BLG design and the application of the properties of the procedure for approximating measurement results by the least squares method, the new BLG has an increased accuracy: 0.1 μGal. Experimental studies confirmed the adequacy of theoretical studies and the feasibility of practical use of the new BLG. Analysis of existing ballistic gravimeters revealed such disadvantage [2] as their high sensitivity to a large number of influencing factors, which, in turn, entails structural complexity, large overall dimensions and weight of gravimeters, as well as their peripheral devices, complexity of processing results, low measurement performance, etc. The task of measuring gravitation acceleration by ballistic methods is essentially reduced to measuring distance and time. This follows, for example, from the analysis of the acceleration dimension. Therefore, the mathematical model must reveal the analytical relationship of the path traveled by the test body with time and external disturbing influences. The most constructive approach to building a model will be such that, on the one hand, the free motion of the test body in the inertial coordinate system is considered, taking into account the vertical gradient of the PST and resistance forces, and on the other hand, the law of motion of some coupled coordinate system is determined, which is displaced under the action of external inertial disturbances and the holding reference system of the gravimeter [2, 3]. The article considers the issues of existing capabilities for measuring the acceleration of gravity using absolute ballistic gravimeters, improving the information processing automation system, and the possibility of further creating a video surveillance system for the process of obtaining results, which should eliminate errors and ensure maximum measurement accuracy.